2020
DOI: 10.1029/2019wr026594
|View full text |Cite
|
Sign up to set email alerts
|

GRACE‐based Mass Conservation as a Validation Target for Basin‐Scale Evapotranspiration in the Contiguous United States

Abstract: Here, we evaluate basin‐scale evapotranspiration (ET) estimates for eleven major river basins in the contiguous United States against a water balance approach with Gravity Recovery and Climate Experiment (GRACE) satellite observations. The relatively precise measurements of large‐scale changes in water mass from GRACE are used to estimate the storage rate term in the terrestrial water budget and consequently provide an estimate, with propagated uncertainty, of basin‐aggregated ET from mass conservation. We app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 65 publications
3
32
0
Order By: Relevance
“…Finally, SSEBop and MOD16 brought little improvement to the water budget closure. The poor performances of MOD16 have already been highlighted by e.g., Pascolini-Campbell et al (2020) in the CONUS, Bhattarai et al (2019) in India.…”
Section: Datasets Suitable In Given Regionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Finally, SSEBop and MOD16 brought little improvement to the water budget closure. The poor performances of MOD16 have already been highlighted by e.g., Pascolini-Campbell et al (2020) in the CONUS, Bhattarai et al (2019) in India.…”
Section: Datasets Suitable In Given Regionsmentioning
confidence: 95%
“…CC BY 4.0 License. larger inter-annual variability (Liu et al, 2016;Pascolini-Campbell et al, 2020;Swann and Koven, 2017) and larger magnitudes (Bhattarai et al, 2019;Long et al, 2014a;Wan et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…We calculated the change in water storage dS/dt using TWSA and a backward difference method (as in Pascolini-Campbell et al, 2020). For TWSA, we used the most recent GRACE RL06 mass concentration (mascon) solution (available online at: https://podaac.jpl.nasa.gov/dataset/TELLUS_GRAC-GRFO_MAS-CON_CRI_GRID_RL06_V2) (Tapley et al, 2004).…”
Section: Water Balance Etmentioning
confidence: 99%
“…Water balance‐based estimates of evapotranspiration (ET) using observations of mass change from the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow‐On (GRACE‐FO) satellites have been found to diverge from state‐of‐the‐art land hydrology assimilation model ET (Castle et al., 2016; Pan et al., 2017; Pascolini‐Campbell et al., 2020; Rodell et al., 2011). A study of the Colorado river basin found satellite‐based ET was ∼14% greater than land surface model (LSM)‐based ET when annually averaged over the basin (Castle et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation